Strengthening the Hompimpa Community through Traditional Game Development in Nongkosawit Village, Gunungpati District, Semarang City - Raharjo, Hermawan Pamot; Wijayanti, Dwi Gansar Santi; Irsyada, Roas; Hendriansyah, Dony Tirta; Nurrafi'u, Gizalias Kusnanda; Suparmi, Suparmi (Jurnal Abdimas, 2025)
One way to maintain the local identity and wisdom of the community is to preserve culture, such as traditional games. Nongkosawit Village is a tourist village that has the potential to preserve culture. However, along with the development of the times and the sophistication of technology, many people, especially the younger generation, have switched from traditional game coaching to modern games. Some other problems include children's lack of knowledge about various traditional games, lack of interest in traditional games, and lack of movers/activists of traditional games. The impact is that children do less physical activity, so that their physical, mental health, and social development are disrupted until the fading of a culture. The purpose of this service activity is to preserve and reintroduce traditional Game Development to the community, especially the younger generation, so that they can actively move. The Hompimpa community, as one of the communities that focuses on the preservation of traditional Game Development, needs to get support in the development and development of its programs to be more effective in cultivating movement in the community. The solution that can be provided is a Strengthening of the Hompimpa Community to re-preserve traditional games in the community in Nongkosawit Village. The implementation methods that will be carried out include a) Activity Preparation, b) Review of Problems in the Field, c) Implementation, d) Program Evaluation, and e) Activity Reporting. This activity was attended by 120 elementary school children, which was held at the Sidosari Field, Nongosawit Village. The result of this service activity is that the Hompimpa Community is consistent in introducing and preserving traditional games. Another positive impact is to cultivate the young generation of Nongosawit Village to actively participate in traditional games. So that a better quality of life is created.